PENGARUH PEMBERIAN JUS JAMBU BIJI DAN TABLET FE TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL DENGAN ANEMIA DI WILAYAH KERJA PUSKESMAS CINERE TAHUN 2022 - Anggraeni, Ayu Kurnia (Politeknik Tiara Bunda, 2022)
Background: Anemia is a global health problem that is quite common, including in Indonesia. This condition is characterized by a decrease in hemoglobin levels in the blood, resulting in a lack of oxygen in the body. Anemia is often associated with various factors such as iron, vitamin B12, or folate deficiency. Research Objective: This study aimed to determine the effect of dragon fruit juice consumption on increasing hemoglobin levels in pregnant women with anemia Research Methods: This cross-sectional study involved all pregnant women in the Juli 2023 (n=10). Hemoglobin levels before and after dragon fruit juice consumption were analyzed using appropriate statistical tests. Research Results: The results showed a significant increase in hemoglobin levels after consuming dragon fruit juice. This indicates that regular consumption of dragon fruit juice has the potential to be an intervention for anemia in pregnant women. Conclusion: This study provides preliminary evidence that dragon fruit juice can be an effective alternative to increase hemoglobin levels in pregnant women . However, further research with a stronger design and a larger sample size is needed to confirm these findings.